PENGARUH PERDAGANGAN INTERNASIONAL, INVESTASI, DAN PEMBIAYAAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI PROVINSI JAMBI - Mar’atur Rahmah; Bambang Kurniawan; Rohana Rohana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The economy can be said to be experiencing growth if the level of economic activity in that period is higher than the previous period. Economic growth is used to describe economic progress and development in a country or region. This research aims to determine the influence of exports, PMA investment and sharia financing on economic growth in Jambi Province. This research is quantitative research using secondary data taken from the Central Statistics Agency (BPS), the One Stop Integrated Investment Service (DPMPTSP), the Industry and Trade Service (Disperindag) and the Financial Services Authority (OJK) with a combination of time series and cross data. section for the 2018-2022 period. The method used is panel data regression with the Fixed Effect Model (FEM) approach. The results of this research show that the t test of the export and sharia financing variables has a positive and significant effect on the economic growth of Jambi Province, the PMA investment variable does not have a significant effect on the economic growth of Jambi Province. Then the results obtained from the f test show that exports, PMA investment and sharia financing simultaneously influence the economic growth of Jambi Province